The effects of knowledge sharing on individual creativity in higher education institutions: Socio-technical view - Joosung Lee; Wenxing Bai (Administrative Sciences, 2018)
Knowledge sharing has multifaceted effects on organizations, such as improving work performance, among which creativity is apparently one of the most important parts. Nevertheless, the effects of knowledge sharing on individuals has not been paid attention sufficiently by previous research. Furthermore, knowledge sharing research mainly concerns business organizations rather than public organizations. This study aims to examine the effects of knowledge sharing on individuals in a higher institution of education in Korea, for which a socio-technical view and social capital theory is used to investigate the important antecedents of knowledge contribution, as well as to examine social and technical facets. This study is the first research regarding the relationship between knowledge sharing and individual creativity, and it also identifies the mediating effects of knowledge sharing on individual creativity at an individual level in a higher education institution.
Keywords: 350; socio-technical view; individual creativity; knowledge sharing